3-Benzyl-7-chloro-9-phenyl-2-tosyl-2,3,3a,4,9,9a-hexahydro-1H-pyrrolo[3,4-b]quinoline - Chinnakali, K. (International Union of Crystallography, 2009)
In the title compound, C(31)H(29)ClN(2)O(2)S, the pyrrolidine ring adopts an envelope conformation with the methine C atom adjacent to the NH group as the flap atom. The tetrahydropyridine ring has a half-chair conformation. The two rings are trans-fused. The chlorobenzene ring and the adjacent phenyl ring form a dihedral angle of 77.9 (1)°. The benzyl phenyl and the tosyl phenyl rings are oriented at a dihedral angle of 88.0 (1)°. In the crystal, molecules are linked into chains along the a axis by N—H⋯Cl and C—H⋯Cl hydrogen bonds and the adjacent chains are cross-linked via C—H⋯π interactions.